GESTUR SISWA SEKOLAH MENENGAH PERTAMA DALAM MEMECAHKAN MASALAH MATEMATIS SECARA BERKELOMPOK - Nur Laili Achadiyah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2017)
This research aimed to describe in detail the students’ gesture in collaborative mathematical problems solving. The results showed that students gestured in solving mathematical problem collaboratively. The students’ gesture is intended to (a) him/her self, (b) others, or (c) him/her self and others. According to the presence or absence of accompanying speech, the students’ gesture may occur (a) before the speech, (b) in conjunction with speech, (c) after the speech, or (d) without speech. The functions of the students’ gesture in collaborative mathematical problems solving are to (1) draw attention to the important aspects of the problem (2) show the position of something in the matter, (3) attract, focus, and keep attention on the important aspects that are being discussed, (4) write something that already exists in the mind as the final form, (5) concrete something that is being considered, and (6) guide or direct the process of thinking.